The effect of anti-PD-1/PD-L1 antibodies combined with VEGF receptor tyrosine kinase inhibitors versus bevacizumab in unresectable hepatocellular carcinoma - Zeng, Hui; Xu, Qi; Wang, Jinyu; Xu, Xiaoqing; Luo, Jun; Zhang, Lei; Luo, Cong; Ying, Jieer; Li, Jingjing (Frontiers in Immunology, 2023)
Introduction: Immune checkpoint inhibition (ICI) plus bevacizumab (BEV) is the standard first-line treatment for unresectable hepatocellular carcinoma (uHCC). We aimed to assess the efficacy and safety of ICI plus bevacizumab and ICI plus receptor tyrosine kinase inhibitor (TKI) in this patient population. Methods: This retrospective single-institution study enrolled 94 patients with uHCC who received ICI plus TKI or bevacizumab as the first-line treatment. Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR) were used to evaluate treatment efficacy. RECIST v1.1 criteria were used to calculate the objective clinical response. Common Terminology Criteria for Adverse Events were used to report and categorize adverse events. Results: By the last follow-up interview on May 15, 2022, there were 57 deaths, and 19 patients did not develop disease progression. Thirty patients received sintilimab/atezolizumab plus bevacizumab (ICI+BEV group), and 64 received ICI plus TKI (ICI+TKI group). The median OS was 430 days (95% CI, 266-NA) in the ICI+TKI group and 498 days (95% CI, 349-NA) in the ICI+BEV group (HR, 1.20; 95% CI, 0.69-2.07; P = 0.52). There was no significant difference between the two groups in the median PFS (182 vs. 221 days, P=0.67). In the ICI+TKI group, the ORR and DCR were 28.1% and 67.2%, respectively. In the ICI+BEV group, the ORR and DCR were 26.7% and 66.7%, respectively. The overall incidence of adverse events was similar between the two groups. Palmar-plantar erythrodysesthesia syndrome (23[36%]) occurred only in the ICI+TKI group. Patients who received ICI+BEV were more prone to upper gastrointestinal bleeding (2 [7%]), with one patient with grade 4 requiring emergency DSA treatment. Conclusion: This study found that ICI+TKI and ICI+BEV as first-line treatments were similar in OS, PFS, and tumor response in uHCC. Different populations are suitable for different regimens because of the different adverse events.